Real-world prognostic factors in autotransplanted multiple myeloma patients with severe renal impairment: study of the Polish Myeloma Study Group - Anna Waszczuk-Gajda; David H. Vesole; Jolanta Małyszko; Artur Jurczyszyn; Tomasz Wróbel; Joanna Drozd-Sokołowska; Piotr Boguradzki; Krzysztof Mądry; Agnieszka Tomaszewska; Jarosław Biliński; Maria Król; Longin Niemczyk; et al. (Archives of Medical Science)
Introduction The prognostic factors in autotransplanted multiple myeloma (MM) patients with concomitant advanced chronic kidney disease (CKD) are poorly understood, limited, and controversial.